Politics of Humanism in Amitav Ghosh’s The Calcutta Chromosome - Qattari, Prakash (Bon Voyage, 2025)
Amitav Ghosh’s The Calcutta Chromosome is a novel about ethical responsibility that deals with medical research. It narrates human’s behavior and inter-personal relationship. This research presents the human psychology, existence and knowledge, in exclusionary perspectives around the world in a span of time. This research explores human activities from other centric perspective. In the beginning, this research presents the westerners’ dominance over the non-westerners. Being an anti-liberal, other centered and sensible how a person can perceive the intellectual task in a period of life is the main finding. For this purpose, the action depends according to belief and values. In the span of time, westerns values seem to exclude the eastern values. The researcher opines that self-centered anti-liberalist concept causes diverse actions. It modifies the binary sight of an action, removes fixity, and changes its actions. It fulfills the gap between enlightenment rationality and rational-sensibility of Levine’s notion of ‘other’. The argument of Descartes’ ‘ cogito ‘ ( self ) is counter argued by Levinas, whose notion of self, talks about the self is separate from the world.